Diseño e implementación de un sistema de control automático para el movimiento del Kit de Robótica Costarricense: Krotic - Espinoza-Quesada, Catalina (Instituto Tecnológico de Costa Rica, 2018)
This report refers to the design and implementation of automatic position and speed control systems for the movement of the robotics kit Krotic. Research is carried out on the design of low cost quadrature encoders and designs with different configurations and sensors are made. Subsequently, performance tests are formulated to select the encoder that best fits the system. With the choice of the encoder that presents the best performance, two control systems are designed that adjust to movement instructions by distance and time. For this, analytical and empirical methods are used to obtain the numerical models of the system and with these models, simulations are carried out to approximate the types of control necessary and the values of the constants for these. For the instructions of movement by distance an angular position control system is elaborated, and for the instructions of movement by time an angular velocity control system. The set of instructions is redesigned in a way that adapts to the control systems, this contains instructions by time and distance, and movements forward, backward, clockwise and counterclockwise. Finally, power consumption measurements are made according to the speed of the servomotors. Convenience speeds are chosen for the high, medium and low battery states to optimize battery life.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018
Keywords: Codificación; Modelos analíticos; Modelos; posiciones; Control; Sistemas; Velocidad; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics